Peningkatan Kesadaran Mahasiswa Terhadap Sejarah Bangsa Melalui Program Kerja Bakti Di Makam Pahlawan Desa Sagu Baru Kecamatan Lawe Bulan Kabupaten Aceh Tenggara - Muhammad Yassir; Rahmat Arfan; Indra Akbar; Desy Puspita; Muhammad Ridha; Geta Ambartiasari; Thona Mutuah Myco (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
Socialization activity was need to do by student at Desa Lawe Sagu Baru Aceh tenggara. Purpose of this activity to increase bonding and solidarity between student university and community. Beside that this activity was doing to increase awareness of student about hero service in wartime. Some activity was doing like painting wall, cutting grass, cleaning rubbish like plastic, bottle, can and fall leaves. With this social activity, student invite community to directly involve to maintain cleanliness dan take care Makan pahlawan which in Desa Lawe Sagu Baru Aceh Tenggara.